Correlation of BDNF, VEGF, TNF‐α, and S100B with cognitive impairments in chronic, medicated schizophrenia patients - Phatcharee Chukaew; Nutthaya Bunmak; Natchaphon Auampradit; Apinya Siripaiboonkij; Witchuda Saengsawang; Woraphat Ratta‐apha (Wiley, 2022)
Abstract Cognitive impairment is a prominent cause of disability in schizophrenia. Although antipsychotic drugs can rescue the psychotic symptoms, the cognitive impairments persist, with no treatment available. Alterations of BDNF, VEGF, TNF‐α, and S100B have been linked to cognitive impairment in several neurological disorders. However, it remains unclear whether their levels are correlated with the cognitive functions of schizophrenia patients. Forty‐one chronic, medicated schizophrenia patients were included in this study. Enzyme‐linked, immunosorbent assays were used to measure the serum concentrations of BDNF, VEGF, TNF‐α, and S100B. Associations between serum protein levels and various domains of the cognitive functions of the schizophrenia patients were observed. We found significant, positive correlations between serum BDNF and the processing speed and attention levels of the patients. Serum VEGF was also positively correlated with their memory and learning functions. In contrast, serum S100B and TNF‐α were negatively correlated with the processing speed and attention of the schizophrenia patients. The findings warrant further investigation of these molecules as potential prognostic markers or treatment targets for cognitive impairment in schizophrenia patients.